Diagnostic value of circular RNAs in colorectal cancer: A systematic review and meta-analysis - Zhao, Zheng; Zhao, Yan; Liu, Yunxin; Zou, Jianjun; Zhu, Yubing (Pathology, research and practice, 2019)
Mounting studies has revealed that circular RNAs (circRNAs) play a key role in tumorigenesis and might serve as promising biomarkers for cancer diagnosis. However, the diagnostic value of circRNAs in colorectal cancer (CRC) remains to be precisely elucidated. All relevant literatures were searched using Cochrane Library, PubMed, Web of Science, EMBASE, CNKI, and WanFang databases up to June 2019. The quality of eligible studies was assessed in accordance with the Quality Assessment of Diagnostic Accuracy Studies-2 system. The summary receiver operator characteristic curve (SROC) and area under SROC (AUC) were applied for the quantitative assessment of diagnostic performance. Threshold effect, subgroup analysis, and meta-regression were adopted to explore the sources of heterogeneity. Deeks’ funnel plot and sensitivity analysis were conducted to examine the publication bias and stability of meta-analysis, respectively. A total of 13 eligible studies involving 2190 subjects and 14 different kinds of circRNAs were enrolled. The pooled sensitivity, specificity, and AUC were 0.78 [95% confidential interval (CI): 0.70-0.84], 0.71 (95% CI: 0.65-0.76), and 0.80 (95% CI: 0.76-0.83), respectively. Subgroup analysis showed that studies involving ≥ 100 cases had higher sensitivity but lower specificity than those involving < 100 cases. Meta-regression revealed that sample size might be the potential source of heterogeneity. Sensitivity analysis and Deeks’ funnel plot indicated that our results were relatively robust and had no publication bias. CircRNAs possess relatively moderate diagnostic accuracy and might serve as potential diagnostic biomarkers for colorectal cancer. Future large-scale studies are needed to confirm the diagnostic value of circRNAs.